Contextual review of physical requirements of refereeing Rugby Union at an elite level - Blair, M. R.; Cronin, J. B.; Nehrer, N. J.; Button, C.; Gill, N. D. (Strength and Conditioning Journal, 2018)
Rugby Union referees often determine the outcome of matches, which highlights the importance of their physical conditioning and decision-making ability. This article reviews the limited pool of research related to the physical demands of refereeing 15-a-side rugby union within the context of match officials from other team sports. Decision-making investigations are critically discussed, and current physical monitoring assessments are presented along with training recommendations for strength and conditioning coaches. For a video abstract of this article, see supplemental digital content 1 (see video, http://links.lww.com/scj/a221).